Building new indicators for researchers’ careers and mobility based on electronic curriculum vitae : the case of the DeGóis Platform - Fontes, Margarida (2008)
(Excerto) It is currently managed by FCT (Council for Science and Technology), which by Law is required to continuously promoting the advancement of scientific and technological knowledge in Portugal, exploring opportunities that become available in any scientific or technological domain to attain the highest international standards in the creation of knowledge, and to stimulate their diffusion and contribution to improve education, health, environment, and the quality of life and well being of the general public. This mission is mainly accomplished through the financing subsequent to the evaluation of the merit of proposals presented by institutions, research teams or individuals in public open calls, and through cooperation agreements and other forms of support in partnership with universities and other public or private institutions. The results of the activities of FCT are, in essence, the additional contributions of individuals, research groups and institutions who have been awarded financing.